Pengaruh Metode Maserasi dan Ultrasonik terhadap Ukuran Partikel Ekstrak Kulit Buah Kakao (Theobroma cacao) - Khairana Zahira Putri, Kheizka; Elsa Prahasti, Anastasia (Jurnal Kedokteran Gigi Terpadu, 2022)
Background: Cocoa’s (T. cacao) pod husk extract substances is one of many natural ingredients that can potentially be used as an alternative to root canal irrigation. The particle size of this active substances will affect its ability to cross the cell membrane. Further research is needed on which extraction method is better to use. Objective: To determine the effect of maceration and ultrasonic methods on the particle size of T. cacao pod husk. Methods: Cocoa pod husk powder was measured using Particle Size Analyzer (PSA) and then extracted by maceration and Ultrasonic Assisted Extraction (UAE) using 80% ethanol as solvent. The particles of both extracts were re-measured using PSA. Data analysis was carried out using paired T-Test and independent T-Test. Result: The particle size of T. cacao pod husk extract with maceration had a significant difference (p<0.05) compared to T. cacao pod husk extract with ultrasonic with a p value of 0.025. The particle size of T. cacao pod husk extract using ultrasonic has a smaller average particle size with an average difference of 114 nm. Conclusion: T. cacao pod husk extract using UAE has a smaller average particle size. This particle size can increase the antibacterial activity of the T. cacao pod husk extract.